English Lessons : The Pedagogy of Imperialism in Nineteenth-Century China - Hevia, James Louis, 1947- (Book collections on Project MUSE., 2003)
A re-evaluation of British Imperialism in nineteenth-century China from the perspective of postcolonial theory.